Donald Trump’s Political Speech: A Critical Issue “us vs them” - Rahmaniah Rahmaniah; Yuni Utami Asih; Bibit Suhatmady (Borneo Educational Journal (Borju), 2022)
Politics is always linked to activities that have an impact on government or societal action and policies. For a variety of reasons, a speech can be a powerful tool, and any speech, particularly one intended to persuade, must be rhetorical. A persuasive speech, such as Donald Trump's, seeks to persuade the audience to accept his idea by making a reasonable claim and providing evidence to support it, because Donald Trump has the potential to be a positive force for the American economy. The purpose of this analysis is to identify how Trump uses discourse about a critical issue (the American economy) to portray a "us versus them" message. Two approaches to analysis were used in this study: Fairclough's CDA (2013) and Van Dijk's (2008). The outcome demonstrated power in his speech and demonstrated the closeness between Trump's administrations; additionally, his speech persuaded the people to accept his speech. As a result, the speech reflected both negative and positive aspects in lauding his administration's accomplishments.